Influence of Compensation, Competence, and Discipline on Employee Performance: A Study at RSUD dr. Sayidiman Magetan - David Zola Mandak; Tatik Mulyati; Ahadiati Rohmatiah (International Journal of Business and Quality Research, 2026)
This research aims to analyze the partial and simultaneous influence of Compensation, Competence, and Discipline on Employee Performance at RSUD dr. Sayidiman Magetan. This study employs a quantitative research design with a sample size of 270 employees. The data analysis techniques utilized include multiple linear regression analysis, t-test (partial), F-test (simultaneous), and the coefficient of determination (R2). The results of the research indicate that: 1) Partially, Compensation, Competence, and Discipline have a significant influence on Employee Performance at RSUD dr. Sayidiman Magetan; 2) Simultaneously, the variables of Compensation, Competence, and Discipline jointly influence Employee Performance at RSUD dr. Sayidiman Magetan; and 3) Discipline is the most dominant variable influencing Employee Performance.